Dokumentasi Perencanaan Strategis Sistem Informasi pada PT. Roda Prima Perkasa - Michelle Patricia Wijaya; Darriel Dapples; Cindy Patricia Kadir; Lionnell Julycell Huang; Mulyati Mulyati (JUMINTAL: Jurnal Manajemen Informatika dan Bisnis Digital, 2026)
This study aimed to design an information systems strategic plan for PT. Roda Prima Perkasa, a metal-based building materials distribution company located in Palembang. The main problem identified was the suboptimal utilization of information systems, particularly in ordering processes, promotion, and customer interaction, which were still handled manually. This study employed a qualitative approach using the Anita Cassidy framework, consisting of the visioning, analysis, direction, and recommendation stages. Several analytical tools were applied, including Porter’s Five Forces, SWOT, PESTLE, Value Chain, and the McFarlan Strategic Grid. The results indicated that PT. Roda Prima Perkasa operated in a highly competitive business environment and required digital transformation to enhance its competitiveness. The existing information systems were primarily operational and had not yet provided significant strategic value. This study proposed the development of an integrated ERP/CRM system, a B2B online ordering website, improvements in information technology infrastructure, and the enhancement of human resource competencies